ICT-SUPPORTED STUDENTS' INDEPENDENT WORK IN THE ESP CONTEXT: THE NEW REALITY IN TERTIARY EDUCATION - Natalia Shumeiko; Alla Nypadymka (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2021)
The article aims at conducting empirical research of university students' readiness to handle independent work while studying the English for Specific Purposes (ESP) course, subject to the availability of Information and Communication Technologies (ICTs). In order to accomplish the objective of the article, a mixed methods research was applied. According to the research methodology, the questionnaires were conducted during the first semester of the academic year 2019/20 and then in the first semester of the academic year 2020/21 at the Kyiv National University of Trade and Economics. The investigation covered the period before the outset of the pandemic when a blended learning approach included instructor-led classroom training and e-learning elements; and then during the time of the COVID-19 pandemic in Ukraine when webucation was in line with the priorities of the training process. The participants of the study were first-year and second-year students of non-linguistic specialities. The scientific research reflected that teaching ESP was focused on enhancing foreign language learning in the particular field of study such as IT, law, trade, marketing, management or economics, to equip students with the oral and written comprehension and speaking skills that they would need to leverage partnerships with international interlocutors in the business community. The obtained results confirmed the high value of the resources available online for studying ESP as an academic discipline in university-level curricula. The analysis of data showed that during the pandemic almost equal percentages of the respondents faced the challenges that accompanied the process of learning English online. Students noted all four proposed options that characterised the disadvantages of completing the assignments independently, namely the communication vacuum, difficulties in choosing supplemental instructional materials, as well as a lack of self-discipline and control. The outcome confirmed the need to assist students' independent work. To meet that demand, the authors carried out a Strength, Weakness, Opportunity, and Threat (SWOT) Analysis related to the use of ICTs within the organising framework of students' independent work while teaching ESP during a pandemic. It has been concluded that the opportunities and threats, as well as the strengths and weaknesses, identified through the SWOT analysis, characterise the advantages, drawbacks and peculiarities that emerge in the process of providing guidance for students' independent work in the study of ESP, integrating them into a coherent whole.